Pulsed laser ablation produced copper nanoparticles (Cuo nps): The influence of time - Adnan N.N.; Razak S.N.A.; Roslan M.S.; Taib N.A.M.; Hasim N.; Amran N.B. (Trans Tech Publications Ltd, 2024)
Indexed by WOS/SCOPUS/ERA